Peningkatan Kompetensi Guru PPKN SMP Dalam Melaksanakan Penilaian Autentik Berdasarkan Kurikulum 2013 - Komarudin Komarudin; Sarkadi Sarkadi; Ahmad Tarmiji Alkhudri (Bahasa Indonesia, 2018)
Abstract Authentic assessment has a strong relevance to the scientific approach to learning that is in accordance with the demands of the 2013 Curriculum. Its existence is very important for teachers to understand. However, in reality there are still teachers who do not understand authentic assessment as an important part of the implementation of the 2013 curriculum. Therefore, it is very important to do community service activities about authentic assessment, especially for PPKn subject teachers at the Junior High School level in Indramayu Regency. The form of P2M activities in the form of workshops with problem solving methods rests on cooperative inquiry. The target audience is 45 PPKn teachers at the Junior High School level in Indramayu Regency. The results of P2M activities showed an increase (1) participants' understanding of the basic concepts of authentic assessment with a score (84) after the workshop and (93) after online mentoring; (2) Understanding of authentic assessment according to the 2013 curriculum with the value of (87) after the workshop and (90) after online assistance; (3) the ability to identify the types and authentic assessment instruments with a value (84) after the workshop and (90) after online assistance; (4) development of instruments, authentic assessment rubrics (80) after workshops and (86) after online mentoring. Abstrak Penilaian authentik memiliki relevansi kuat terhadap pendekatan ilmiah dalam pembelajaran yang sesuai dengan tuntutan Kurikulum 2013. Keberadaannya sangat penting dipahami oleh para guru. Namun, dalam kenyataannya masih terdapat guru yang belum memahami penilaian autentik sebagai bagian penting dari implementasi kurikulum 2013. Oleh karena itu, sangat penting dilakukan kegiatan pengabdian kepada masyarakat tentang penilaian autentik, khususnya bagi guru mata pelajaran PPKn Tingkat SMP di Kabupaten Indramayu. Bentuk kegiatan P2M berupa workshop dengan metode pemecahan masalah bertumpu pada cooperative inquiry. Khalayak sasaran adalah guru PPKn Tingkat SMP di Kabupaten Indramayu sebanyak 45 orang. Hasil kegiatan P2M menunjukkan peningkatan (1) pemahaman peserta mengenai konsep dasar penilaian autentik dengan nilai (84) sesudah workshop dan (93) sesudah pendampingan online; (2) Pemahaman penilaian autentik menurut kurikulum 2013 dengan nilai (87) sesudah workshop dan (90) sesudah pendampingan online; (3) kemampuan mengidentifikasi jenis-jenis dan instrumen penilaian autentik dengan nilai (84) sesudah workshop dan (90) sesudah pendampingan online; (4) pengembangan instrumen, rubrik penilaian autentik (80) sesudah workshop dan (86) sesudah pendampingan online.